Introduction to behavioral research methods - Leary, Mark R. (England : Pearson, 2014)
Rigorous, yet readable. The author presents the material with sufficient elaboration, explanation, and examples that not only interest the student, but make it understandable. Introduction to Behavioral Research Methods incorporates the four basic approaches to behavioral research (descriptive research, correlational research, experimental research, and quasi-experimental research), and shows students how to conceptualize questions, measure variables, design studies, and analyze data. Chapters on research ethics and scientific writing (including the most recent version of APA style
Includes bibliographical references and index.
Keywords: Psychology -- Research -- Methodology